2018
DOI: 10.1051/0004-6361/201832683
|View full text |Cite
|
Sign up to set email alerts
|

Hot bubbles of planetary nebulae with hydrogen-deficient winds

Abstract: Context. The first high-resolution X-ray spectroscopy of a planetary nebula, BD +30 • 3639, opened the possibility to study plasma conditions and chemical compositions of X-ray emitting "hot" bubbles of planetary nebulae in much greater detail than before. Aims. We investigate (i) how diagnostic line ratios are influenced by the bubble's thermal structure and chemical profile, (ii) whether the chemical composition inside the bubble of BD +30 • 3639 is consistent with the hydrogen-poor composition of the stella… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…An optical spectroscopic study has shown that the N + and O ++ ionized regions have an expansion velocity of 28 km s −1 and 35.5 km s −1 , respectively (Bryce & Mellema 1999). It is well known that BD+30 contains a central hot bubble (e.g., Heller et al 2018), which is also revealed as an extended X-ray emission (Leahy et al 2000). The ionization and shock heating may result in a radial pressure gradient, causing an acceleration of the ionized gas.…”
Section: Discussionmentioning
confidence: 99%
“…An optical spectroscopic study has shown that the N + and O ++ ionized regions have an expansion velocity of 28 km s −1 and 35.5 km s −1 , respectively (Bryce & Mellema 1999). It is well known that BD+30 contains a central hot bubble (e.g., Heller et al 2018), which is also revealed as an extended X-ray emission (Leahy et al 2000). The ionization and shock heating may result in a radial pressure gradient, causing an acceleration of the ionized gas.…”
Section: Discussionmentioning
confidence: 99%
“…However, when there is sufficient signal to constrain the hot bubble abundances, the chemical composition is often found to be discrepant with both the central star and nebular abundances (e.g., Toalá et al 2019). Mixing between the central star and nebular abundances is included in theoretical efforts to understand hot bubble X-ray emission (Steffen et al 2008;Toalá & Arthur 2016;Heller et al 2018;Toalá & Arthur 2018). In the X-ray-emitting temperature ranges of hot bubbles, the abundances of carbon, nitrogen, oxygen, neon, and iron have the strongest influence on the spectral shape of the X-ray emission.…”
Section: Model I: Varying Elemental Abundancesmentioning
confidence: 99%
“…Hot bubbles are expected to scale with the square of the fast wind velocity; however, Chandra and XMM-Newton observations indicate that plasma temperatures are much cooler than expected (e.g., Kastner et al 2008;Ruiz et al 2013). Understanding the origin of these cooler plasma temperatures is an unresolved area of research being explored with a variety of approaches (Soker & Kastner 2003;Akashi et al 2007;Steffen et al 2008;Toalá & Arthur 2016;Heller et al 2018;Toalá & Arthur 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some planetary nebulae are sources of X-ray emission, which may have a diffuse component coming from the nebula (e.g., Chu et al 2001, Heller et al 2018) and a point-source component associated with the central star (Freeman et al 2014, Montez et al 2015. X-ray emission of O stars, which is supposed to originate in their winds (Feldmeier et al 1997), shows a strong correlation between the X-ray luminosity and stellar luminosity roughly as L X ≈ 10 −7 L (Nazé 2009).…”
Section: Comparison With Observationsmentioning
confidence: 99%